2023
DOI: 10.1021/acs.langmuir.3c01847
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Heat Flow between Charged Nanoparticles and an Aqueous Electrolyte

Reza Rabani,
Mohammad Hassan Saidi,
Ali Rajabpour
et al.

Abstract: Heat transfer through the interface between a metallic nanoparticle and an electrolyte solution has great importance in a number of applications, ranging from nanoparticle-based cancer treatments to nanofluids and solar energy conversion devices. However, the impact of the surface charge and dissolved ions on heat transfer has been scarcely explored so far. In this study, we compute the interface thermal conductance between hydrophilic and hydrophobic charged gold nanoparticles immersed in an electrolyte using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 73 publications
0
1
0
Order By: Relevance
“…This thermal resistance, due to the disparity in the electronic and vibrational characteristics of the two materials in contact, is called ITR and is given by R K = normalΔ T J normalq where J q is the heat flux across the interface and Δ T is the temperature difference between the materials in contact. Computational studies have proven valuable in developing an understanding of the fundamental mechanism of interfacial thermal transport between solid–fluid interfaces, including graphene–ionic liquid (IL) interfaces which are more relevant for supercapacitor thermal transport . Qian et al investigated the ITR and structure at the interface between graphene and the IL and observed that the molecular orientation of ions near the solid surface dominates the degree of heat transfer at the imidazolium-based IL-graphene interface.…”
Section: Introductionmentioning
confidence: 99%
“…This thermal resistance, due to the disparity in the electronic and vibrational characteristics of the two materials in contact, is called ITR and is given by R K = normalΔ T J normalq where J q is the heat flux across the interface and Δ T is the temperature difference between the materials in contact. Computational studies have proven valuable in developing an understanding of the fundamental mechanism of interfacial thermal transport between solid–fluid interfaces, including graphene–ionic liquid (IL) interfaces which are more relevant for supercapacitor thermal transport . Qian et al investigated the ITR and structure at the interface between graphene and the IL and observed that the molecular orientation of ions near the solid surface dominates the degree of heat transfer at the imidazolium-based IL-graphene interface.…”
Section: Introductionmentioning
confidence: 99%